Uranium (VI) ion removal using a novel high adsorption COFs/GO/CH aerogel nanocomposite for wastewater treatment - Mohammed D. Majeed; Mahmoud Roushani (Results in Chemistry)
Uranium is a highly radioactive metal that poses significant health risks. Developing efficient methods for removing uranium from wastewater is crucial, as uranium contamination can have far-reaching consequences. The newly synthesized adsorbent material, COFs/GO/CH aerogel nanocomposite contains covalent organic frameworks, graphene oxide and chitosan. This adsorbent is tested under different conditions, including contact time, concentration, pH, dosage, temperature, and the presence of other ions. The maximum adsorption capacity of COFs/GO/CH for U(VI) as 1191 mg/g at pH 6.0. This adsorbent not only demonstrated high efficiency in eluting uranium from aqueous solutions, but also showed affinity towards uranium in mixed metal solutions. The adsorption process followed the pseudo-second-order kinetic model and Langmuir isotherm, indicating a combination of physisorption and chemisorption mechanisms. The structure of COFs/GO/CH is characterized using various analytical techniques such as Fourier transform infrared spectroscopy (FT-IR), field emission scanning electron microscopes (FE-SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron microscope (TEM), X-ray diffraction (XRD) Brunauer-Emmett-Teller (BET) and zeta potential (ZP). Importantly, the nanocomposite COFs/GO/CH aerogel is found to be stable, ready for regeneration and reuse over five successive cycles, while maintaining efficient U(VI) removal from wastewater.